2017
DOI: 10.1038/ngeo2999
|View full text |Cite|
|
Sign up to set email alerts
|

A spatially resolved estimate of High Mountain Asia glacier mass balances from 2000 to 2016

Abstract: High Mountain Asia hosts the largest glacier concentration outside the polar regions. These glaciers are important contributors to streamflow in one of the most populated areas of the world. Past studies have used methods that can only provide regionally-averaged glacier mass balances to assess the High Mountain Asia glacier contribution to rivers and sea level rise. Here we compute the mass balance for about 92 % of the glacierized area of High Mountain Asia using time series of digital elevation models deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

79
1,000
9
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 900 publications
(1,097 citation statements)
references
References 51 publications
79
1,000
9
9
Order By: Relevance
“…For Abramov Glacier, we find mass balances in between the results derived by Gardelle et al (2013) and Brun et al (2017) 15 based on the comparison of DEMs, overlapping within the respective uncertainty ranges. Mass changes reported by Gardelle et al (2013) are most likely too positive as SRTM C-Band penetration depth into snow Berthier et al, 2016) might have been underestimated for the cold and dry snow of accumulation areas (Dehecq et al, 2016 For Golubin Glacier, the inferred mass balance is in close agreement with the geodetic mass change reported by Bolch (2015) (Fig.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…For Abramov Glacier, we find mass balances in between the results derived by Gardelle et al (2013) and Brun et al (2017) 15 based on the comparison of DEMs, overlapping within the respective uncertainty ranges. Mass changes reported by Gardelle et al (2013) are most likely too positive as SRTM C-Band penetration depth into snow Berthier et al, 2016) might have been underestimated for the cold and dry snow of accumulation areas (Dehecq et al, 2016 For Golubin Glacier, the inferred mass balance is in close agreement with the geodetic mass change reported by Bolch (2015) (Fig.…”
mentioning
confidence: 68%
“…12b). Brun et al (2017) agreement between all available mass balance assessments was found (Fig. 12c).…”
mentioning
confidence: 75%
See 3 more Smart Citations